Penerapan prosedur operasional standar budi daya tanaman jeruk ramah lingkungan untuk menekan infestasi kutu perisai merah Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae): Implementation of environmentally friendly standard operational procedures for citrus plant cultivation to suppress infestation of red scale Aondiella aurantii (Maskell) (Hemiptera: Diaspididae) - Wicaksono, Rudi Cahyo; Endarto, Otto; Istianto, Mizu; Budiarto, Kurniawan; Tarigan, Rasiska; Triasih, Unun; Wuryantini, Susi (Perhimpunan Entomologi Indonesia, 2024)
Citrus is a popular horticultural crop planted in different areas in Indonesia. The needs for fruits increases every year, yet production cannot fulfill market demand. One of the contraints are the red scale pest attacks Aonidiella aurantii (Maskel). The implemeintation of standard operating procedure (SOP) in citrus cultural practices is expected to have effects on the population and intensity of red scale attacks. The research was carried out from January to August 2020 on farmer's orchards located at the center of citrus production in Batu, East Java, Indonesia. This experimental study used the research design theory method. The plots were devided into 2 conditions; first, the plots applied SOP, such as regular pruning, sanitation, and organic fertilizer application. While, the second was the conventional plots representing the common farmer maintenance, farmer of not pruning and cleaning weeds throughout the garden, and using NKP inorganic fertilizer. Every evaluated plot covered 1,500 m2, and 10 plants were systematically sampled from every plot. The parameters included numbers of attacked fruits, the abundance of natural enemies and attack intensity of A. aurantii that were taken from the cardinal directions. The results of the study showed that the implementation of SOP was able to significantly reduce population density and intensity of A. aurantii pest attacks and was able to increase the abundance of natural enemies and the quality of citrus fruit when compared to conventional citrus cultivation methods.